Boundary Layer Flow Past a Wedge Moving in a Nanofluid. (13th May 2013) - Khan, Waqar A.; Pop, I.
Abstract : The problem of steady boundary layer flow past a stretching wedge with the velocity u w ( x ) in a nanofluid and with a parallel free stream velocity u e ( x ) is numerically studied. It is assumed that at the stretching surface the temperature T and the nanoparticle fraction C take the constant values T w and C w, respectively. The ambient values (inviscid fluid) of T and C are denoted by T ∞ and C ∞, respectively. The boundary layer governing partial differential equations of mass, momentum, thermal energy, and nanoparticles recently proposed by Kuznetsov and Nield (2006, 2009), are reduced to ordinary differential equations along with the corresponding boundary conditions. These equations are solved numerically using an implicit finite-difference method for some values of the governing parameters, such as β, λ, Pr, Le, N b, and N t, which are the measure of the pressure gradient, moving parameter, Prandtl number, Lewis number, the Brownian motion parameter, and the thermophoresis parameter, respectively.